Role of Social Workers in Facilitating of the Poverty Alleviation Program in Indonesia - Anwar Sitepu (Asian Social Work Journal, 2017)
This paper aims to describe the idea of the professionalization of handling the poor in Indonesia, namely through the establishment of a social worker assistant the poor. Poor Social Worker Companion who is a professional social worker was appointed assistant the poor. Professionalization companion deemed urgent. The poor handling challenge because it is more difficult. The fact is: 1) the number of poor people in Indonesia is still high; 2) the pace of decline slowed down the number of poor people; 3) There are a large number of residents are not poor are vulnerable to fall back into poverty. On the other hand, the poor management program through its joint (Kube) has not been effective enough. Recent research shows that only 40 percent Kube established in 2013 is still active when checked 30 months later. This finding is in line with the results of evaluations conducted since decades ago. This condition is alarming and needs improving the poor handling system significantly. One of the components is seen as strategic human resources. Suggested remedies are by appointment professional social workers to become a partner. The social worker assigned duties and functions facilitate the handling of the poor in a certain area within a certain time. The function of the social worker suggested the poor companion is: a) guide the community to collect data on available data the poor by name by address in its territory; b) verification and validation of data the poor; c) selecting program participants the poor handling; d) perform reference handling the poor; e) advocate for the Poor that all rights are met; f) The poor family counseling; g) make public the guidance in the handling of the Poor; h) monitoring and evaluating the progress of the Poor; i) make the case record the poor family; and h) report on the implementation of tasks. The social worker is deemed appropriate to perform this task because they are trained to help people meet their mission needs, support, knowledge, values , and skills.